Análise do sistema de gestão de algumas organizações militares do Exército Brasileiro com base nos critérios do PNQ - Pinho, Francisco Delmo Crespio de (2004)
The present work looks for answers to subjects about organizational performance and propose an instrument of diagnose self-evaluation to verify the analysis of the organizacional management of some Military Organizations (MO) of Brazilian Army (BA). This instrument, constructed by from a theoretical study on evaluation methodologies, a self-evaluation research was created and applied, using the Criterions of Excellency of the National Quality Award - NQA 2003, adapted for military segment of the BA. The instrument has the purpose of creating an evaluation model, to check how is the level of management of those organizations and their results. There were applied questionnaires in six OM of the BA located in Rio de Janeiro, whose results were properly analyzed. An analysis of organizations profile was also accomplished, supported by the conceptual model defined. The obtained result of that comparative study checked the validity of the research instrument, taking us to conclude about the need and importance of the Criterions of the NQA-2003, as an improvement propel to the improvement of the performance in the management of public organizations, face to the demands of the new worldwide society with relation to proffer better services